The Use of Non-Standard Indonesian Language Varieties in Non-Formal Communication in the Student Environment of UPN Veteran East Java - Dandi Azaidane; Muhammad Alfredo Putra; Nisrina Ramadhani Putri Kuswara; Sheila Aisyah Ariani; Najja Septamevia; Bagas Novardi Abdurrahman (KIRANA : Social Science Journal, 2026)
This research explores the use of informal Indonesian language variations in non-formal communication among students at UPN Veteran Jawa Timur. Using a qualitative method, the study gathers data from surveys and observations within the context of social interactions on campus. The results show that students frequently use informal language, including colloquial expressions and slang, as a form of self-expression and group identity formation. Social media has a significant influence in shaping these language variations. While the use of informal language strengthens social bonds and creates comfort in communication, there are concerns regarding the understanding of formal language in academic settings. These findings provide insights into student communication dynamics and the role of language in their social lives.